Reproduction of cultural and social capital in nineteenth century Spanish regimental bands of the Philippines - Tan, Arwin Q. (2014)
Band tradition in the Philippines traces its origins to the regimental bands of the Spanish colonial period. As a representation of social power, the regimental band was a symbol of Spain’s hierarchical relation with the colony. The elevation of a Filipino musician to the rank of the bands’ highest position, the bandmaster, enabled the accumulation of cultural capital, providing him a highly influential position in his local community that is almost equivalent to his Spanish counterpart.

This paper examines how music was used as cultural capital by some Filipinos, framed in the band tradition of the Spanish military regiments of the late nineteenth century Philippines. Using Bourdieu’s theory of cultural and social capital and his concept of habitus, this paper aims to trace the development of a new social class and the reproduction of its accumulated cultural capital. The eventual attainment of prestige as a result of occupying the highest position in the Spanish regimental bands afforded the bandmasters significant influence in their communities that transmuted cultural capital into social, symbolic, even economic capital.
Keywords: History -- Spanish regime, 1521-1898; Music as cultural capital; Bands (Musical groups); Cultural capital